Collaborative Governance in Handling Stunting: A Success Study in Gintungkerta Village, Karawang District - Ghiffari Faizi Ramadhan; Lina Ariani; Karien Febriantin (Journal of Social Science Utilizing Technology, 2024)
Background. Stunting is a condition caused by malnutrition which is related to chronic nutritional insufficiency. Stunting can occur while the fetus is still in the womb and will become visible when the child is 2 years old. Therefore, stunting can cause death in babies and children, as well as causing sufferers to get sick easily and have below average cognitive abilities. Purpose. This research aims to analyze the role of collaborative governance in handling stunting in Gintungkerta Village, Karawang Regency. Method. This research is included in the type of qualitative research with a case study approach. Qualitative research methods. The data sources that will be used in this research consist of primary data and secondary data. The data will later be obtained through data collection techniques from related sources and parties based on research conducted regarding Collaborative Governance in Handling Stunting in Gintungkerta Village. The data collection techniques used in the research were carried out using various sources, both from primary sources and secondary sources, which were carried out using techniques such as observation, interviews, questionnaires, documentation.  Results. The results of this research show that the facilitative leadership by the DPPKB is not optimal, especially in terms of budget and facilitation. The institutional design is good with the involvement of the government, private and community sectors. The collaboration process includes face-to-face dialogue, building trust, commitment and mutual understanding, with positive interim results in reducing stunting in Gintungkerta Village. Conclusion. The high stunting rate in Gintungkerta Village encourages collaboration between the government, community and private sector through the DASHAT program, even though DPPKB support is not yet optimal in terms of budget and resources. Overall, the collaboration went well thanks to adequate initial conditions, strong institutional design, and shared commitment and understanding among stakeholders.